ANALISIS STABILITAS HARGA BERAS DI KOTA KUPANG - Melgiana Medah (Partner, 2020)
Trade Act No. 7 of 2014 article 26 paragraph 3 mandates that” in guaranteeing the supply and stabilization of prices of staple goods and essential goods, the Minister established pricing policies, stock management and logistics as well as export and import management”. Rice food supply circulating in Kupang city 75% comes from Java and Sulawesi, 25% is local rice (Melgiana and Chris 2018. The amount of rice outside NTT circulating in the market will affect the stability of rice prices in the city of Kupang. This research is a survey activity, data collected sourced from primary and secondary data using descriptive methods. The sampling technique uses a purposive sampling of 92 traders spread across 4 wholesale markets (Oesapa, Oeba, Inpres and Oebobo) of Kupang city. The results showed that the price of rice in the city of Kupang ahead of the holiday was unstable. The increase in normal prices towards the holiday increased by 2%. In addition there is a price difference between the highest retail price set by the government and the price prevailing in the market in the city of Kupang.               Keyword : price stability, rice